Gold-catalyzed cyclisation by 1,4-dioxidation - Claus, Vanessa; Molinari, Lise; Büllmann, Simon; Thusek, Jean; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2019)
Amide-substituted diynes were cyclized in the presence of a cationic gold catalyst and an external nucleophile leading to 1-indenones and 1-iminoindenones. The electron-donating features of the nitrogen atom enable the formation of a reactive ketene iminium ion, which can be trapped by either diphenyl sulfoxide or anthranil as nucleophiles in a subsequent oxidation step, providing substituted inden-1-on-3-carboxamides.